Curbing Online Banking Frauds (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
In modern economy, banks form the core of financial transactions. In present context, use of IT by banks to provide financial services has increased convenience and accessibility for citizens. E-banking or online banking has become more popular with the increase in number of internet and smartphone users. During the period of Covid-19 online shopping for consumable and durable items became more common between masses. Debit cards, credit cards, UPI, internet banking, etc. are various ways to make cashless transactions led towards cashless economy. These mediums are convenient to use, but due to a lack of awareness, people suffer financial losses. Cybercriminals are constantly collecting personal information through new techniques of cyber attacks like phishing, ATM skimming, hacking, ransomware etc. and through various inducements like the lottery, free charges, cashback, loan waivers and payment-related problems like sim blocking, KYC updates etc. Banks send alerts to consumers from time to time through advertisements and other means of publicity. In WhatsApp, Telegram and other messaging app some false warning messages are send like electricity will be cut off, bank accounts will freeze, the insurance policy will lapsed, etc it manipulates consumers to click on the given link which causes the occurrence of a cyber fraud. As a result, despite being vigilant, they become victims of online fraud. During 2011 a total of 4,093 cases of bank fraud were registered whereas in 2023 a total of 13,530 cases, as reported by RBI, are registered. This shows a severe trend in the number of cases of fraud across the turn of a decade. To avoid online fraud, it is suggested not to receive or click on suspicious calls, links or emails. The important banking information like banking password, OTP, and ATM PIN, should not be shared with anyone.